Pencegahan Covid 19 RW 2 & 3 Desa Kenteng Sempor Dengan Teori Keperawatan Betty Neument Menggunakan CAP - Marsito, Marsito; Saraswati, Rina; Sarwono, Sarwono; Ernawati, Ernawati; Mustoleh, Mustoleh (Prosiding University Research Colloquium, 2022)
The total population of Kenteng Village is 4680 people, of which in the 02 and 03 pillars there are 1048 people (22.39%) of the 7 community units. Given the high mobility and still in a state of the COVID-19 pandemic, it is necessary to look at preventing the spread of Covid. Seeing these results, the researchers used Betty Neuman's nursing theory with the Community as Partner approach. With the aim of looking at core data on age, safety and transportation such as wearing masks, maintaining distance, and washing hands for health services that have been vaccinated against Covid 19. The sample is all residents of the 02 and 03 Kenteng Village Community Units totaling 1048 people. From the results of the core data study, it was found that the majority of people aged over 18 years were 798 people (88.5%), safety and transportation using masks were sometimes used by 507 people (48%), doing hand washing sometimes there were 665 people (58). %) and keeping a distance the result is never keeping a distance there are 604 people (58%). The number of people who have been vaccinated is 735 people (70.1%). That Betty Neuman's Nursing theory uses the Community as Partner approach in community nursing to see how to prevent covid 19. Thus, Betty Neuman's nursing theory can be used in the prevention of Covid 19 in the community.